Causal Relationship of Skin Microbiota on Psoriasis: A Mendelian Randomization Study - Chen Y; Zhuang Z; Rao Z (Dove Medical Press, 2024)
Yangjia Chen,1,* Zhaocheng Zhuang,1,* Zhixiang Rao2 1Department of Preventive Medicine, School of Health, Quanzhou Medical College, Quanzhou, Fujian, 362011, People's Republic of China; 2School of Humanities and Management, Fujian University of Traditional Chinese Medicine, Fuzhou, 350122, People's Republic of China*These authors contributed equally to this workCorrespondence: Yangjia Chen, Department of Preventive Medicine, School of Health, Quanzhou Medical College, Quanzhou, Fujian, 362011, People's Republic of China, Email 2015018@qzmc.edu.cnObjective: Epidemiological investigations have indicated an association between skin microbiota imbalance and psoriasis, however, the causal relationship has not been confirmed through Mendelian randomization (MR). MR employed genetic instrumental variables (IVs) to evaluate the causal relationship between skin microbiota and psoriasis, providing new insights for potential treatments.Methods: Summary statistics for psoriasis and related traits were available from FinnGen R10 and United Kingdom Biobank (UKB) consortium. The genome-wide association studies (GWAS) on skin microbiota in three skin microenvironments came from two population-based German cohorts. Several selection processes were used to determine the optimal instrumental variables. Five MR methods were performed and different sensitivity analyses approaches yield robustness evidence under different assumptions.Results: 449 SNPs were employed as IVs for 53 bacterial genera, with F-statistics between 20.18 and 42.44, indicating no evidence of weak instrument bias. Bacteroides was associated with psoriasis from UKB in IVW (OR, 95% CI: 0.914, 0.869- 0.961; P < 0.001, PB-H = 0.007). The taxon was also associated with psoriasis vulgaris (IVW: OR, 95% CI, 0.918, 0.872- 0.967; P = 0.001, PB-H = 0.054) and psoriasis and related disorders (IVW: OR, 95% CI, 0.915, 0.875- 0.957; P < 0.001, PB-H = 0.008). Consistent causal estimates were identified in terms of both magnitude and direction, indicating a protective effect of Bacteroides.Conclusion: The MR study found that Bacteroides in the antecubital fossa may protect against psoriasis, offering genetic proof that skin microbiota helps prevent the condition.Keywords: skin microbiota, psoriasis, Mendelian randomization, genus Bacteroides, autoimmune disease, AD